2020
DOI: 10.2147/cmar.s283169
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cost-Effectiveness Analysis of Maintenance Olaparib in Patients with Metastatic Pancreatic Cancer and a Germline BRCA1/2 Mutation Based on the POLO Trial</p>

Abstract: Objective The phase III POLO trial demonstrated that olaparib as maintenance therapy for metastatic pancreatic cancer patients with a germline BRCA mutation had greater efficacy than placebo, but maintenance olaparib places an economic burden on patients. This study evaluated the cost-effectiveness of olaparib as maintenance therapy based on the POLO trial (NCT02184195). Methods A three-state Markov model (progression-free survival [PFS], progressive disease [PD] and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…In particular, Wu and Shi (2020 ) in the United States found that olaparib was cost-effective with an ICER at $191,596 per PFS-QALY, which was below the $200,000 threshold but not the case when modeling was based on overall survival data ($265,290 per QALY). In China, Zhan et al (2020 ) identified an ICER at $34,122 per QALY which did not support cost-effectiveness at the WTP threshold of $28,255, although the ICER drastically dropped to $14,563 per QALY when the drug cost was calculated based on the donation plan for ovarian cancer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, Wu and Shi (2020 ) in the United States found that olaparib was cost-effective with an ICER at $191,596 per PFS-QALY, which was below the $200,000 threshold but not the case when modeling was based on overall survival data ($265,290 per QALY). In China, Zhan et al (2020 ) identified an ICER at $34,122 per QALY which did not support cost-effectiveness at the WTP threshold of $28,255, although the ICER drastically dropped to $14,563 per QALY when the drug cost was calculated based on the donation plan for ovarian cancer.…”
Section: Resultsmentioning
confidence: 99%
“…All the articles performed sensitivity analyses to assess the factors which potentially impacted the cost-effectiveness of PARP inhibitors. Out of 20 studies, 17 highlighted that the drug price was a significant driver of the ICER ( Secord et al, 2013 ; Smith et al, 2015 ; Wallbillich et al, 2016 ; Institute for Clinical and Economic Review, 2017 ; Zhong et al, 2018 ; Dottino et al, 2019 ; Armeni et al, 2020 ; Barrington et al, 2020 ; Gonzalez et al, 2020 ; Muston et al, 2020 ; Penn et al, 2020 ; Su et al, 2020 ; Wu and Shi, 2020 ; Zhan et al, 2020 ; Cheng et al, 2021 ; Leung et al, 2021 ; Olry de Labry Lima et al, 2021 ). In the United States system, to be cost-effective in treating recurrent ovarian cancer among BRCAmut patients, major cost reduction to $3,000–6,400 per cycle was warranted for olaparib, niraparib, and rucaparib, which was up to 76% reduction at the WTP of $100,000 ( Secord et al, 2013 ; Smith et al, 2015 ; Wallbillich et al, 2016 ; Dottino et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of the included studies are shown in presented in S2 Table . Overall, 19 studies were published after June, 2019, including 9 in 2020 [ 22 30 ], 7 in 2021 [ 31 37 ], and 3 2022 [ 38 40 ]. Studies were conducted from the United States (US) (n = 13) [ 16 – 20 , 23 28 , 38 , 40 ], China (n = 5) [ 27 , 30 , 32 , 39 , 40 ], Singapore (n = 2) [ 31 , 34 ], Japan [ 21 ], Italy [ 22 ], and Spain [ 33 ].…”
Section: Resultsmentioning
confidence: 99%